Analisis Hubungan Pemanfaatan Teknologi Informasi Sebagai Penunjang Prestasi Mahasiswa Fasilkom UNSRI melalui Metode Uji Chi-Square - Yunus, Hedi; Barata, Gusti; Ibrahim, Ali (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2019)
The chi-square test is a hypothesis test of the comparison between the frequency of observation and the frequency of expectations based on a particular hypothesis in each case or the data taken to be observed. From the research test with the title "Testing the relationship between the use of IT on student achievement levels". In total 50 respondents from the scope of the Faculty of Computer Science, Sriwijaya University, and after spss test and significance test can be produced that t count = 0.867 <t table = 9,488 means that Ho is accepted so that the conclusion is there is a relationship between the use of IT to the level of student academic achievement